Fatty Acid Profile and Antioxidant Capacity of Dabai (Canarium odontophyllum L.) : Effect of Origin and Fruit Component - Shanti Faridah, Salleh; Olaide Olawunmi, Ajibola; Crilio, Nolasco-Hipolito; Ahmad, Husaini; Carvajal, Zarrabal-Octavio; Samuel, Lihan; Gbadebo, Clement Adeyinka; Firdaus, R. Rosli; Idris, Adewale Ahmed; Mohamed Zaky, Zayed; Rosmawati, Saat (MDPI, 2022)
In the present work, the influence of geographical location on the fatty acid profiles, antioxidant potential, as well as cytotoxicity of edible dabai fruit fractions (kernel, skin, and pulp) were analyzed. The fatty acid profiles were determined by Gas Chromatography (GC), and the antioxidant activity was quantified with free 2,2-diphenyl-1-picr/ylhdrazyl, while the cytotoxicity was assessed by the brine shrimp lethality test. The results showed that the samples from Sibu, Serian, and Kapit geographical locations had a high content of the saturated fatty acids, ranging from 46.63% to 53.31% in the three fractions. The highest mono-saturated fatty acids (MUFA) content was found in Sibu. Serian and Kapit kernel fractions MUFA, however, ranged from 21.2% to 45.91%. No fatty acid composition was detected in Bentong and Kanowit. The fatty acid composition and DPPH free radical scavenging antioxidant activity of dabai were statistically independent using a multivariate analysis in different localities in Malaysia. The skin fraction had a more appreciable antioxidant potential and toxicity level than the pulp and kernel fractions. The highest antioxidant activity (EC50 198.76 ± 1.06 µg/mL) with an LC50 value of 1387.22 µg/mL was obtained from the Sibu skin fraction. Therefore, the fatty acid composition, antioxidant, as well as cytotoxicity analyses of the extracts from different localities indicated that “geographical location” remarkably influenced fatty acid composition, antioxidant activity, and toxicity.